Penyuluhan Bahaya Narkoba dan Antisipasi Pergaulan Bebas Remaja Usia Sekolah di Kabupaten Sinjai Sulawesi Selatan - Safriadi (Universitas Hasanuddin, 2020)
Drug trafficking in Sinjai Regency is really worrying. The number of drug users is increasing. Thus, the drug business in Sinjai seems promising.This can be seen by the number of people arrested by the police regarding drug users and dealers. The problem that is happening now and also becomes a problem of partners is the lack of knowledge of students about narcotics and illegal drugs, which has an impact on the inability to explain it to them.Beside that, there is a phenomenon that at school there are several cases of early-age marriage occurring as a result of promiscuity. These cases are of concern to the teacher and school committee.Based on this, our opinion is very urgent, there are efforts to increase knowledge related to narcotics and various causes, also Output and Outcome for this activity stated as follow: (1) Completion of socialization activities with a minimum number of participants of 50 people, (2) Increasing of knowledge of students about narcotics, types, characteristics and effects,the creation of a drug-free environment in schools and promiscuity. (3)There is no longer the occurrence of early marriage as a result of premarital sex with adolescents in Sinjai 13 High School particularly and society generally.